CISG AND REGIONAL SALES LAW: FRIENDS OR FOES? - Coetzee, Juana (Journal of Law, Society and Development, 2015)
Â Economic co-operation and integration brings with it a need to harmonise mechanisms for the regulation of international trade, not only at a public-law level between states but also at a private-law level between traders inter partes. It is often forgotten that differences in the substantive law applicable to a contract function as a non-tariff barrier to trade. Because international trade facilitates economic development, the focus in this article is on the harmonisation of sales laws. Traditionally, private law harmonisation has been conducted by international private or inter-state organisations that specialise in the harmonising of law at a global level. Today, private organisations and groups devoted to harmonising business laws, as well as regional economic integration organisations, are also pursuing legal harmonisation. Global, regional and domestic laws now all exist in the same area of the law, which can give rise to duplication of efforts and problems with the co-existence of global and regional sales law. This article will discuss these issues with reference to the United Nations Convention on Contracts for the International Sale of Goods (CISG) and selected regional laws in considering whether regional harmonisation can act as a stepping stone towards increased harmonisation at a global level or whether it is to be viewed as a threat to global integration and harmonisation.